Gabriel Tortella Casares (Dir.), Leonardo Caruana de las Cagigas, José Luis García Ruiz, Alberto Manzano Martos y Jerònia Pons Pons. Historia del seguro en España. Madrid, Fundación Mapfre, 2014, 530 págs., ISBN: 978-84-9844-418-6. - Espuelas Barroso, Sergio (Investigaciones de Historia Económica, 2019)
Sin resumen